Neurobehavior of newborn infants exposed prenatally to methadone and identification of a neurobehavioral profile linked to poorer neurodevelopmental outcomes at age 24 months. - Trecia A Wouldes; Lianne J Woodward (PLoS ONE, 2020)
The abuse of prescription opioids and heroin by women of childbearing age over the past decade has resulted in a five-fold increase in the number of infants born opioid-dependent. Daily opioid substitution treatment with methadone is associated with less maternal illicit opioid use and improved antenatal care. However, research on the neurobehavioral effects of daily prenatal exposure to methadone on the infant is limited. Using the NICU Network Neurobehavioral Scale (NNNS), we compared the neurobehavior at birth of 86 infants born to opioid-dependent mothers receiving methadone treatment (MMT) with 103 infants unexposed to methadone. Generalized linear models, adjusted for covariates, showed methadone exposed infants had significantly poorer attention, regulation, and quality of movement. They were also significantly more excitable, more easily aroused, exhibited more non-optimal reflexes, hypertonicity, and total signs of stress abstinence. Maternal MMT was also associated with more indices of neonatal abstinence, including: CNS, visual, genitourinary (GI), and state. Latent profile analysis of the NNNS summary scores revealed four distinct neurobehavioral profiles with infants characterized by the most disturbed neurobehavior at birth having the poorest clinical outcomes at birth, and poorer cognitive and motor development at 24 months of age.